Quantifying the value of RFID and the EPCglobal architecture framework in logistics - Uckelmann, Dieter (Springer Berlin Heidelberg, 2012)
The "EPCglobal Architecture Framework" is currently the most accepted technical approach to the Internet of Things and provides a solid foundation for building Business-to-Business information networks based on unique identifications of 'things'. Lately, the vision of the Internet of Things has been extended to a more holistic approach that integrates sensors as well as actuators and includes non-business stakeholders. A detailed look at the current state of the art in research concerning cost and benefit estimations is provided and the limits of Cost Benefit Sharing for RFID-based IT-infrastructures are explained. In this work a market driven evaluation based on sales potential of information is developed. Simple technical means for aggregation of micro values to a billable amount are discussed. The requirements for electronic billing infrastructure are defined and a matching e-billing solutions for an evaluation scenario is presented, providing a technical infrastructure to evaluate and bill product-related information in a future Internet of Things, based on an extended EPCglobal Architecture. Further opportunities and threats are discussed to provide an overview of its future potential. As a result it will contribute to the sustainable success of the Internet of Things itself.